Conocimiento en prevención oral en gestantes. - Higuera Sánchez, Diego Mauricio (2025)
Pregnancy represents a unique and transformative period in a woman’s life, marked by significant biological, physical, and psychological changes. These changes can unfortunately have negative consequences for oral health. Recognizing this impact, it becomes crucial to implement early preventive strategies aimed at empowering pregnant women to embrace responsible and safe motherhood. Indeed, proactive monitoring throughout pregnancy is vital for ensuring healthy fetus development. Furthermore, diet, nutrition, and the prevention of oral cavity diseases are indispensable factors during both the prenatal and postnatal phases. To gain a deeper understanding of this critical area, this research aimed to analyze the existing body of knowledge regarding oral health prevention among pregnant women. This was achieved through a systematic review of 714 original articles published between 2020 and 2025, sourced from the PubMed, VHL Regional Portal, Google Scholar, Scielo, and Cochrane databases, and selected based on predefined inclusion and exclusion criteria. The methodological framework for this analysis is characterized by a mixed, non-experimental, descriptive, and cross-sectional approach